Giant Negative T Waves and QT Prolongation in Non-cardiogenic Pulmonary Edema: A Case Report and Review of Literature - Mansour, Abdallah M (Cureus, 2018)
Giant negative T-waves have been linked to several cardiac and non-cardiac conditions. However, the presence of giant negative T-waves with QT prolongation in the setting of non-cardiogenic pulmonary edema is a rarely reported, female predominant, and poorly understood electrocardiographic phenomenon. We report a case of a 28-year-old white female who presented with acute diarrhea and was admitted due to acute kidney injury caused by a hemolytic uremic syndrome (HUS). She was managed with multiple blood product transfusions, plasma exchange, and hemodialysis. Subsequently, she developed acute pulmonary edema requiring intubation and urgent hemodialysis. During this acute event, a unique electrocardiographic finding of anterolateral giant negative T-wave and QT prolongation progressively developed and began resolving with the resolution of the pulmonary edema. In addition to our case, 12 cases were reported upon review of the literature with similar electrocardiography (ECG) findings in the setting of non-cardiogenic, non-ischemic pulmonary edema. Giant negative T-waves can be associated with non-cardiac pulmonary edema. Recognition of this rare Wellen’s-like electrocardiographic pattern in a patient without cardiac ischemia is crucial, especially in young females. Basic science and clinicopathological correlation studies are needed to understand the pathophysiology and prognosis behind these ECG findings.